How do you find the Maclaurin series for #1/(1+x)^3#?
1 Answer
I got
#1 - 3x + 6x^2 - 10x^3 + cdots# ,
or
#1/2sum_(n=0)^(N) (-1)^(n) (n+2)(n+1)x^(n)# .
I did it the normal way with derivatives, but I also showed a way to do it using the old power series way where you start from
NORMAL WAY
The normal/easier way to do it is to modify the Taylor series so that
#stackrel("Taylor Series")overbrace(sum_(n=0)^(N) (f^((n))(a))/(n!)(x-a)^n) => stackrel("Maclaurin Series")overbrace(\mathbf(sum_(n=0)^(N) (f^((n))(0))/(n!)x^n))#
#= (f(0))/(0!) + (f'(0))/(1!)x + (f''(0))/(2!)x^2 + (f'''(0))/(3!)x^3 + cdots#
We can take the derivative a few times. I'd recommend you do this first, instead of in the process of writing out the sum itself.
#color(green)(f^((0))(x)) = f(x) = color(green)(1/(1+x)^3)#
#color(green)(f'(x)) = -3(1+x)^(-4) = color(green)(-3/(1+x)^4)#
#color(green)(f''(x)) = -3*-4(1+x)^(-5) = color(green)(12/(1+x)^5)#
#color(green)(f'''(x)) = 12*-5(1+x)^(-6) = color(green)(-60/(1+x)^6)#
So let's see what we get. The Maclaurin series becomes:
#= (f(0))/(0!) + (f'(0))/(1!)x + (f''(0))/(2!)x^2 + (f'''(0))/(3!)x^3 + cdots#
#= (1/(1+(0))^3)/1 + (-3/(1+(0))^4)/1 x + (12/(1+(0))^5)/2 x^2 + (-60/(1+(0))^6)/6 x^3 + cdots#
#= color(blue)(1 - 3x + 6x^2 - 10x^3 + cdots)#
OLDER WAY; TAKES LONGER
Technically, the Maclaurin series for this can actually be derived from what you should have been taught as the power series based on
We know that
If we modify
Our steps are:
- Differentiate once to get
#-1(1-x)^(-2)*-1 = 1/(1-x)^2# . - Differentiate again to get
#-2*(1-x)^(-3)*-1 = 2*1/(1-x)^3# . - Multiply by
#1/2# . - Change
#1 - x# to#1 + (-x)# . That means we substituted#-x# in place of#x# !
Therefore, if we do the same thing to the power series, we get what you would call the "power series" for
Step 1:
#d/(dx)[1 + x + x^2 + x^3 + x^4 + x^5 + cdots]#
#= 1 + 2x + 3x^2 + 4x^3 + 5x^4 + cdots# for#n = 1# to#n = N# .
Step 2:
#d/(dx)[1 + 2x + 3x^2 + 4x^3 + 5x^4 + cdots]#
#= 2 + 6x + 12x^2 + 20x^3 + cdots# for#n = 2# to#n = N# .
Step 3:
#1/2(2 + 6x + 12x^2 + 20x^3 + cdots)#
#= 1 + 3x + 6x^2 + 10x^3 + cdots# for#n = 2# to#n = N# .
Step 4:
Finally, substitute
#= 1 + 3(-x) + 6(-x)^2 + 10(-x)^3 + cdots#
#= 1 + 3x(-1)^1 + 6x^2(-1)^2 + 10x^3(-1)^3 + cdots#
#= color(blue)(1 - 3x + 6x^2 - 10x^3 + cdots)# for#n = 2# to#n = N# .
which is the same result as we got before! We just now know that the first term has shifted two indices relative to the power series for
So, the sum notation for the power series would end up having gone through the above steps as well. Note that for step 4, by replacing
#sum_(n=0)^(N) x^n# (starting at#1/(1-x)# )
Finally, to bring it back to an index of
So, add
#=> color(blue)(1/2sum_(n=0)^(N) (-1)^(n) (n+2)(n+1)x^(n) = 1/(1+x)^3)#